2018
DOI: 10.1515/intag-2016-0095
|View full text |Cite
|
Sign up to set email alerts
|

Selected physical properties of various diesel blends

Abstract: A b s t r a c t. The quality determination of biofuels requires identifying the chemical and physical parameters. The key physical parameters are rheological, thermal and electrical properties. In our study, we investigated samples of diesel blends with rapeseed methyl esters content in the range from 3 to 100%. In these, we measured basic thermophysical properties, including thermal conductivity and thermal diffusivity, using two different transient methods -the hot-wire method and the dynamic plane source. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 24 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…The dependencies between the dynamic viscosity and temperature of two bio-oils (Plahyd N and Plahyd S) were determined, indicating an exponentially decreasing trend. Hlaváčová et al (2018) confirmed that rheological data are important for product quality evaluation, engineering calculations and process design. The knowledge and understanding of material behaviour is crucially important for determining the size and energy requirements of the material.…”
Section: Introductionmentioning
confidence: 60%
“…The dependencies between the dynamic viscosity and temperature of two bio-oils (Plahyd N and Plahyd S) were determined, indicating an exponentially decreasing trend. Hlaváčová et al (2018) confirmed that rheological data are important for product quality evaluation, engineering calculations and process design. The knowledge and understanding of material behaviour is crucially important for determining the size and energy requirements of the material.…”
Section: Introductionmentioning
confidence: 60%
“…They studied the dynamic viscosity-temperature dependence of two bio-oil types (namely Plahyd N and Plahyd S) and recorded exponentially decresing trends. Hlaváčová et al (2018) argue that rheological data are important for product quality evaluation, engineering calculations and process design. It is necessary to know and understand the behaviour of different materials to determine the size and energy requirements of associated equipment and production processes.…”
Section: Introductionmentioning
confidence: 99%